Duration of SARS-CoV-2 shedding and infectivity in the working age population: a systematic review and meta-analysis - Rahmani, Alborz; Dini, Guglielmo; Leso, Veruscka; Montecucco, Alfredo; Kusznir Vitturi, Bruno; Iavicoli, Ivo; Durando, Paolo (La Medicina del Lavoro, 2022)
Background: During the COVID-19 pandemic, working age individuals have been implicated in sustaining the resurgence of SARS-CoV-2 infections, and multiple outbreaks have been observed in several occupational settings. In this regard, Occupational Physicians play a crucial role in the management of infected workers, particularly in the safe return-to-work of subjects after clinical resolution. To this end, knowledge of the duration of the infective phase in the working age population is essential, taking into account previous evidence suggesting that PCR positivity does not coincide with virus viability. Methods: A systematic review and meta-analysis, searching major scientific databases, including PubMed/MEDLINE, Scopus and Web of Science, were performed in order to synthesize the available evidence regarding the mean and maximal duration of infectivity compared to the mean and maximal duration of viral RNA shedding. A subgroup analysis of the studies was performed according to the immunocompetent or immunocompromised immune status of the majority of the enrolled individuals. Results: Twenty studies were included in the final qualitative and quantitative analysis (866 individuals). Overall, a mean duration of RT-PCR positivity after symptom onset was found equal to 27.9 days (95%CI 23.3-32.5), while the mean duration of replicant competent virus isolation was 7.3 days (95%CI 5.7-8.8). The mean duration of SARS-CoV-2 shedding resulted equal to 26.5 days (95%CI 21.4-31.6) and 36.3 days (95%CI 21.9-50.6), and the mean duration of SARS-CoV-2 infectivity was 6.3 days (95%CI 4.9-7.8) and 29.5 days (95%CI 12.5-46.5), respectively considering immunocompetent and immunocompromised individuals. The maximum duration of infectivity among immunocompetent subjects was reported after 18 days from symptom onset, while in immunocompromised individuals it lasted up to 112 days. Conclusions: These findings suggest that the test-based strategy before return-to-work might not be warranted after 21 days among immunocompetent working age individuals, and could keep many workers out of occupation, reducing their livelihood and productivity.